The Role of Collective Bargaining in the Global Economy Negotiating for Social Justice - Hayter, Susan (Edward Elgar Publishing, 2011)
This book examines the ways in which collective bargaining addresses a variety of workplace concerns in the context of today's global economy. Globalization can contribute to growth and development, but as the recent financial crisis demonstrated, it also puts employment, earnings and labour standards at risk. This book examines the role that collective bargaining plays in ensuring that workers are able to obtain a fair share of the benefits arising from participation in the global economy and in providing a measure of security against the risk to employment and wages. It focuses on a commonly neglected side of the story and demonstrates the positive contribution that collective bargaining can make to both economic and social goals. The various contributions examine how this fundamental principle and right at work is realized in different countries and how its practice can be reinforced across borders. They highlight the numerous resulting challenges and the critically important role that governments play in rebalancing bargaining power in a global economy. The chapters are written in an accessible style and deal with practical subjects, including employment security, workplace change and productivity, and working time. The Role of Collective Bargaining in the Global Economy will prove essential for postgraduate students in industrial and labour relations, human resource management, economics and business studies, as well as industrial relations practitioners and researchers.